2017
DOI: 10.1108/gm-03-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting women’s aesthetic labour to fly high in the Chinese airline Industry

Abstract: Purpose Drawing upon the existing theoretical and empirical sourced knowledge of aesthetic labour and gender, this paper aims to explore the exploitation of women’s aesthetic labour in the Chinese airline industry and the underlying causes from a contextual point of view. Design/methodology/approach This qualitative study has emerged from a broader research project which aimed to explore women’s experiences of work-family conflict and their career aspirations in the Chinese airline industry in which aestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This existing work has focused on how embodied identities and appearance come to change once women are within an occupation or organization; that is, once they become socialized according to a given habitus (Adamson & Salmenniemi, ; Anderson et al, ; Elias et al, ; Entwistle, ; Haynes, ; Mears, ; Ren, ). By focusing on women's transition from outside of a professional environment into one, this article has demonstrated the impact of understandings of bodily/aesthetic capital of a given context on those outside of it, trying to get in, expanding the use of this concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This existing work has focused on how embodied identities and appearance come to change once women are within an occupation or organization; that is, once they become socialized according to a given habitus (Adamson & Salmenniemi, ; Anderson et al, ; Elias et al, ; Entwistle, ; Haynes, ; Mears, ; Ren, ). By focusing on women's transition from outside of a professional environment into one, this article has demonstrated the impact of understandings of bodily/aesthetic capital of a given context on those outside of it, trying to get in, expanding the use of this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Bourdieu's theories of capital and habitus and their further expansion to bodily/aesthetic capital enable an understanding of the embodied impact of different contexts on women's self-presentation and how and why change comes to occur (Anderson et al, 2010;Bourdieu, 1984Bourdieu, [2010Bourdieu, ], 1986Elias et al, 2017;Haynes, 2012). The development of the term aesthetic labour gave name to the unpaid work employees undertake to meet organizational appearance requirements, requirements that often reflect broader social inequalities (inequality regimes) (Acker, 2006(Acker, , 2012Donaghue, 2017;Ren, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research into management and the sociology of work has shown how recruitment, particularly of young men and women is not based on learned skills and acquired qualifications alone but increasingly on gendered appearances and the "suitability" of a person and often weighted with idealized gender-related aspects (Bradley, 2016;Simpson, 2014;Wolkowitz, 2006;Hochschild, 1983). This is audible in employees' narratives describing the need for branding (Vallas and Cummins, 2015) and aestheticizing the job and the work (Ren, 2017;Witz et al, 2003;Warhurst and Nickson, 2007). Several researchers suggest that the current discourse on personal branding and the gendering of work are indeed truly pervasive among jobseekers for all expert jobs (Vallas and Cummins, 2015;Ren, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is audible in employees' narratives describing the need for branding (Vallas and Cummins, 2015) and aestheticizing the job and the work (Ren, 2017;Witz et al, 2003;Warhurst and Nickson, 2007). Several researchers suggest that the current discourse on personal branding and the gendering of work are indeed truly pervasive among jobseekers for all expert jobs (Vallas and Cummins, 2015;Ren, 2017). The evidence also suggests an interesting shift in the definitions of gendered work and the demands that recruited experts face (Vallas and Cummins, 2015).…”
Section: Introductionmentioning
confidence: 99%